(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the times of COVID-19, everyone was suffering from depression and anxiety due to the COVID-19 pandemic and the nationwide lockdown. Everyone was afraid of what would happen in the future. What will be our livelihood? No one has any idea what will happen. When will the lockdown open? Due to all these reasons, an atmosphere of fear was created among the people and due to this they were suffering from depression and anxiety. Covid-19 not only affected the individual livelihood but also the investment behavior of the investors. The purpose of this paper is to study and describe several biases in investment decision-making during covid-19, through the review of research articles in the area of behavioral finance. It also includes some of the analytical and foundational work and how this has progressed over the years to make behavioral finance an established and specific area of study. The study includes behavioral patterns of individual investors.In the present-daybehavioral finance is becoming an important part of the decision-making process because it heavily influences the investor’s decision-making.